The Effects Of Core Shell Impact Modifier On Properties And Crystallization Behaviour Of Poly(Lactic) Acid - Borhan, Adibah (2018)
Polylactic acid (PLA) was melt-blended with different contents (0 to 30 wt%) of a commercially available core shell impact modifier (CSIM). Neat PLA and PLA/CSIM blends were prepared via an internal mixer and compression molded into test specimens. Thermal, mechanical and morphological properties of neat PLA and PLA/CSIM blends were studied. The neat CSIM showed shell, interphase, and core regions when observed under transmission electron microscopy (TEM). Each region in the neat CSIM presented different glass transition temperature. The Fourier transform infrared spectroscopy (FTIR) confirmed that the shell and core of the neat CSIM was made of polymethyl methacrylate (PMMA) and polybutyl acrylate (PBA), respectively. An increased in CSIM content slightly decreased the ability of PLA to crystallize and/or re-crystallize, and the cold crystallization temperature shifted to higher temperatures. The matrix PLA showed good compatibility with the PMMA shell of CSIM. This was confirmed by the dynamic mechanical analysis (DMA) tests. In the thermogravimetric analysis (TGA), both of the neat PLA and CSIM displayed single step decomposition. Upon addition of CSIM, the stress-strain curves presented that the brittleness of neat PLA increased without the improvement in ductility. Tensile stress, tensile modulus, and elongation at break of PLA decreased; yet, the notched and un-notched impact strength increased as CSIM content increased. Scanning electron microscopy (SEM) micrographs revealed that with the addition of CSIM contents of 5 to 30 wt%, the fractured surface became rougher than neat PLA. Voids were observed which likely caused by the pull-out of CSIM during fracture. The clarity of the PLA was tested using chromameter. Incorporation of CSIM did not affect the clarity of the PLA except at 30 wt% contents of CSIM. The isothermal crystallization kinetics of neat PLA and PLA/CSIM blends were studied by differential scanning calorimetric (DSC) and data obtained were analyzed with the Avrami equation. The results showed that the crystallization rate is controlled by the crystallization temperature and the incorporation of CSIM content. The maximum crystallization rate, τ½ was observed when PLA was blended with 1 wt% CSIM and isothermally crystallized at 105 °C. The result trend for degree of crystallinity (Xc) are comparable to the crystallization rate (τ½) versus crystallization temperature (Tc). The increased in higher Tc ≥ 110 °C has made the mobility of PLA molecular segment become easy to facilitate resulting in the increase of Xc. Based on the Hoffman-Weeks equation, the equilibrium temperature (